2015
DOI: 10.1007/s00221-015-4323-8
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric saccade reaction times to smooth pursuit

Abstract: Before initiating a saccade to a moving target, the brain must take into account the target’s eccentricity as well as its movement direction and speed. We tested how the kinematic characteristics of the target influence the time course of this oculomotor response. Participants performed a step-ramp task in which the target object stepped from a central to an eccentric position and moved at constant velocity either to the fixation position (foveopetal) or further to the periphery (foveofugal). The step size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…It has 55 been well established that the probability of saccade occurrence is minimized during pursuit 56 initiation if the change in position and velocity are in opposite directions and balanced in 57 magnitude such that the target recrosses the initial fixation position in 200 ms (Rashbass, 58 1961). Target trajectories that recross the fixation position after a slightly longer or shorter 59 duration tend to evoke an intermediate probability of saccade occurrence with highly variable 60 latency (Bieg et al, 2015). Similarly during pursuit maintenance, it was observed that the ratio 61 between position and velocity error correlates well with the occurrence of saccades and roughly 62 correlates with saccade latency (de Brouwer et al, 2002b).…”
Section: Introduction 29mentioning
confidence: 92%
See 3 more Smart Citations
“…It has 55 been well established that the probability of saccade occurrence is minimized during pursuit 56 initiation if the change in position and velocity are in opposite directions and balanced in 57 magnitude such that the target recrosses the initial fixation position in 200 ms (Rashbass, 58 1961). Target trajectories that recross the fixation position after a slightly longer or shorter 59 duration tend to evoke an intermediate probability of saccade occurrence with highly variable 60 latency (Bieg et al, 2015). Similarly during pursuit maintenance, it was observed that the ratio 61 between position and velocity error correlates well with the occurrence of saccades and roughly 62 correlates with saccade latency (de Brouwer et al, 2002b).…”
Section: Introduction 29mentioning
confidence: 92%
“…We have developed a model of the saccade decision mechanism during visually guided 388 pursuit in which saccade confidence (defined as the log-probability ratio of position error to the 389 right vs left of the fovea) is computed from predictive estimates of position error and temporally 390 accumulated to trigger saccades upon threshold crossing. This decision mechanism reproduces 391 the Rashbass paradigm, where saccades occurrence during pursuit initiation is minimized if the 392 target recrosses the initial fixation position in 200 ms (Bieg et al, 2015;Rashbass, 1961). The 393 model also reproduces the behavioural observation that saccade occurrence is minimized when 394 the time-to-foveation following a step-ramp during steady-state pursuit is between 40 and 180 395 ms and qualitatively reproduces the distribution of long-latency saccades evoked by step-ramps 396 in and around this time-to-foveation range (de Brouwer et al, 2002b).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…There are additional low-level factors that might further be predicted to modulate both overt and covert visual attention during smooth-pursuit, such as the speed of the moving target, and the spatial locations of where covert shifts of attention are directed. Saccade latencies to stimuli presented during smooth-pursuit have been found to increase as target speed increases (Bieg et al, 2015;Seya & Mori, 2012). An SSVEP index of overt attention throughout the overt tracking of a moving target would allow for further clarification of how covert shifts of attention are influenced by target speed, and whether the effects pertain to the strength of covert shifts, the timing of such shifts, or both.…”
Section: Discussionmentioning
confidence: 99%